2016
DOI: 10.1080/10934529.2015.1109410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of zeolite NaA membrane from fused fly ash extract

Abstract: Zeolite-NaA membranes were synthesized from an extract of fused South African fly ash on a porous titanium support by a secondary growth method. The influence of the synthesis molar regime on the formation of zeolite NaA membrane layer was investigated. Two synthesis mixtures were generated by adding either aluminium hydroxide or sodium aluminate to the fused fly ash extract. The feedstock material and the synthesized membranes were characterized by X-diffraction (XRD), scanning electron microscopy (SEM) and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We then characterized the chemical composition of synthesized Na-A and Na-X samples with XRF. The result of XRF on Na-A sample indicates that it contains 44.64% SiO 2 , 37.29% Al 2 O 3 , 18.22% Na 2 O, 3.80% CaO, 3.36% Fe 2 O 3 , 3.06% TiO 2 , 0.55% MgO and 0.41% K 2 O and the corresponding Si/Al molar ratio is 1.48 and is typical for commercial Na-A, while that for the Na-X sample is 5.12 [ 30 , 61 , 62 ]. The high Si/Al molar ratio of Na-X is due to the introduction of silica sol to get phase-pure Na-X [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then characterized the chemical composition of synthesized Na-A and Na-X samples with XRF. The result of XRF on Na-A sample indicates that it contains 44.64% SiO 2 , 37.29% Al 2 O 3 , 18.22% Na 2 O, 3.80% CaO, 3.36% Fe 2 O 3 , 3.06% TiO 2 , 0.55% MgO and 0.41% K 2 O and the corresponding Si/Al molar ratio is 1.48 and is typical for commercial Na-A, while that for the Na-X sample is 5.12 [ 30 , 61 , 62 ]. The high Si/Al molar ratio of Na-X is due to the introduction of silica sol to get phase-pure Na-X [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…We then characterized the chemical composition of synthesized Na-A and Na-X samples with XRF. 48 and is typical for commercial Na-A, while that for the Na-X sample is 5.12 [30,61,62]. The high Si/Al molar ratio of Na-X is due to the introduction of silica sol to get phase-pure Na-X [60].…”
Section: Characterization Of Zeolite Na-a and Na-xmentioning
confidence: 99%
“…20 19 2 (12) iron for example, which may influence the zeolite crystallisation process. [3][4][5][6][7][8][9] Cations are known to play an essential part in the zeolite crystallisation process and influence the type of zeolite structure formed. This is due to the limited structure directing effect of cations in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications include CFA utilisation for mine back-filling, as well as agricultural remediation of soil and water treatment using modified CFA [17,23]. Another major area of research in CFA valorisation is the production of value-added, porous materials such as zeolites (i.e., zeolitisation) as well as metal extraction/recovery [24][25][26][27][28][29][30][31][32][33][34][35]. As South Africa is largely reliant on coal for energy production [15], CFA research and the development of various CFA valorisation technologies remain major priorities.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the glassy, aluminosilicate phase of CFA contained the majority of the REE content and a process involving size classification, magnetic separation and hydrothermal treatment was proposed as a method of enriching the REE content of CFA [42]. Zeolitisation is a common method utilised in the transformation of the Si and Al content in CFA into a crystalline, porous material with high industrial value [24][25][26][28][29][30][31][32][33][34]. The distributional fate of elements found in CFA during the process of zeolitisation by two different methods (a two-step process and solid fusion-assisted process) was previously reported in literature [26].…”
Section: Introductionmentioning
confidence: 99%